The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.5194/egusphere-egu23-835
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of climatic season changes in Ukraine during 21st century based on an ensemble of 34 RCM projections of Euro-CORDEX

Abstract: <p>The last decade proved to be the warmest in Ukraine for the whole period of instrumental weather observations. Recent and projected future warming will cause changes in the duration of climatic seasons in Ukraine with corresponding shifts in dates of their start and end.</p> <p>As specified by the Expert Team on Climate Change Detection and Indices, climatic seasons are determined as periods from the first day after the start of a year to the first date after 1 July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The forecasts of scientists (Krakovska et al, 2017), (Martazinova & Shchehlov, 2018) predict some further increase in precipitation in the study region.…”
Section: Analysis Of Table 2 and Integrated Diagrams In Figmentioning
confidence: 93%
See 2 more Smart Citations
“…The forecasts of scientists (Krakovska et al, 2017), (Martazinova & Shchehlov, 2018) predict some further increase in precipitation in the study region.…”
Section: Analysis Of Table 2 and Integrated Diagrams In Figmentioning
confidence: 93%
“…According to estimates of mathematical modeling of regional climate processes in Ukraine, Poland, and in the Central European region as a whole, trends in the growth of precipitation amounts will persist in the study region, most forecasts do not foresee a significant decrease in the amount of precipitation (Krakovska et al, 2017;Zolina et al al., 2014;Didovets et al, 2020).…”
Section: Precipitation Regime In the Region At The Beginning Of The 2...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Fang et al [47] stated that for hydrological modeling aspects, bias correction for relative humidity and wind has the least significance. Additionally, the findings of Krakovska et al [48] mentioned RCMs and that the satellite-observed cloud cover product has the least biases. Therefore, as the present study focuses on climate conditions at ground level, bias-corrected climate variables (temperature, precipitation, and relative humidity) were taken into consideration, with raw climate variables such as cloud cover and wind.…”
Section: Gis-based Hci Computation and Visualizationmentioning
confidence: 97%